The Effect of Problem-Based Learning Models Through Blended Learning on Students' Collaborative Ability on Excretion System Subject of class XI SMA Negeri Plus Riau Province - Regina, Angel; Yustina, Yustina; Daryanes, Febblina; Putra, Riki Apriyandi (Pascasarjana Universitas Negeri Malang (UM), 2024)
This study investigates the impact of implementing a Problem-Based Learning (PBL) model integrated with Blended Learning on enhancing students’ collaborative abilities. Conducted in class XI of SMA Negeri Plus Riau Province during the 2021/2022 academic year, the research utilized a control group design to compare the collaborative skills of students in an experimental class, which employed the PBL model, with those in a control class. The study assessed four key indicators of collaborative ability: working productively, valuing opinions, compromising, and sharing responsibility. The findings revealed that students in the experimental class showed significant improvements in all four indicators compared to the control class. Specifically, the experimental group demonstrated better time management, greater respect for diverse viewpoints, enhanced ability to find common ground, and a stronger sense of shared responsibility. These results suggest that the combination of PBL and Blended Learning fosters a more engaging and effective learning environment, promoting active participation, critical thinking, and teamwork. The study concludes that adopting such pedagogical approaches can enhance collaborative skills among students, making them better prepared for future challenges that require cooperation and problem-solving. This research provides valuable insights for educators seeking to implement innovative teaching strategies to improve educational outcomes and equip students with essential 21st-century skills.DOI: 10.17977/jps.v12i32024p117